Chlamydia, gonorrhea, and HIV-1 prevalence among five populations of women in the Czech and Slovak Republics - Kacena, K A; Dohnal, K; Benesova, V; Grivna, M; Deliopolu, J; Trýzna, R; Horák, J; Gaydos, C A; Quinn, T C (Sexually transmitted diseases, 2001)
BACKGROUND: Five populations at risk for sexually transmitted diseases (STDs) in the Czech and Slovak Republics were sampled. GOAL: To estimate prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, and HIV-1 infections. STUDY DESIGN: Urine specimens were collected serially from women at a Prague prenatal clinic (n = 134), a Prague dermatovenerealogy clinic (n = 91), sex workers from northern and central Bohemia (n = 35), students from a northern Bohemian school (n = 217), and Gypsies from Jarovnice, Slovakia (n = 128). These specimens were tested for chlamydia and gonorrhea using a ligase chain reaction pooling algorithm, and for HIV using an enzyme immunoassay confirmed by Western blot. RESULTS: The prevalence of chlamydia was 2.2% (95% CI, 0.4-6.4) in the prenatal clinic, 5.5% (95% CI, 1.8-12.4) in the STD clinic, 22.9% (95% CI, 10.4-40.1) among street sex workers, 8.2% (95% CI, 3.6-15.6) among sexually active female high school students, and 3.9% (95% CI, 1.3-8.9) among Gypsy women. Gonorrhea was found in only two populations: 2.2% (95% CI, 0.3-7.7) in the STD clinic, and 2.9% (95% CI, 0.1-14.9) among sex workers. No HIV-1 infection was detected. CONCLUSIONS: Urine screening was an efficient and accurate method for identifying groups at risk for STDs in the Czech Republic and Slovakia because sample collection was fast and noninvasive, and potential participation bias was reduced by high acceptability.
Keywords: dospělí; Blotting, Western; těhotenství; Humans; Prevalence; Slovakia; chlamydiové infekce; Ligase Chain Reaction; Czech Republic; Pregnancy Complications, Infectious; gonorea; zjišťování skupinových postojů; ELISA; Slovenská republika; Surveys and Questionnaires; Česká republika; Enzyme-Linked Immunosorbent Assay; ROC Curve; Adult; ligasová řetězová reakce; Adolescent; sexuálně přenosné nemoci; průzkumy a dotazníky; Chlamydia Infections; ženské pohlaví; ROC křivka; Gonorrhea; western blotting; HIV-1; mladiství; lidé; infekční komplikace v těhotenství; prevalence; Pregnancy; HIV Infections; HIV infekce; Focus Groups; Sexually Transmitted Diseases; Female